The educational, academic and sporting trajectory of young basketball athletes: A scope review (Research, Society and Development, 2021)
Objective: to map studies that analyze the educational, academic and sporting trajectory of young basketball athletes. Method: The scope review was carried out using the methodology developed by the Joanna Briggs Institute (JBI) and includes research studies carried out with young basketball athletes. Studies published in English, Spanish or Portuguese were considered using a date limit of 10 years in originating documents such as articles, dissertations and theses that were organized in ascending order of year. Government documents were intentionally selected to support the sport with an emphasis on basketball. The search strategy followed the natural process of document screening, with the search carried out in the following databases: CAPES, BVS, SciELO, SportDiscus, Scopus, Web of Science, PubMED/MEDLINE and ERIC journals. The descriptors “Educational Environment”, “Human development”, “Basketball” were used. Results: From 297 studies found, 9 articles were selected, these being punctual studies, which portrayed the interest in the sporting trajectory/sports career of young basketball athletes and the environment in which they are inserted. Conclusion: Of the selected studies, some bring the scientific support of the environment through the theory of Urie Bronfenbrenner (Bioecological Theory) that show the environment as an incitement to development or delay, impacting their educational, academic and sports trajectory. Most documents used a qualitative approach and all have similarities in their problem, however it is partially concluded that studies connecting the sports trajectory related to the basketball environment using the qualitative method are punctual, it is noted that the existence is more unusual. documents that use quantitative methods.